Implementation of E-Module Flip Pdf Higher Order Thinking Skills to Improve Geography Learning Outcomes at Senior High School Level - Novianti Sofyan, Diana; Herpratiwi, Herpratiwi; Firdaus, Rangga; Nurwahidin, Muhammad (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to implement e-modules based on Higher Order Thinking Skills (HOTS) in geography learning at SMA 1 Terbanggi Besar, Central Lampung. The research method used was quantitative with a mixed method approach, involving 30 respondents from class X. The results showed that the implementation of e-modules can significantly improve students' learning outcomes. The results showed that the application of e-modules can significantly improve student learning outcomes, with 29 respondents obtaining high categories in N-gain. Although there are obstacles in implementing HOTS-based learning models, the results show that the use of digital media can encourage students' critical and creative thinking skills. This study recommends the integration of e-modules in the learning process to prepare students for the challenges of the 21st century.